Remote experiment manager with mobile node in test infrastructure for wireless networks - Almeida, Rafael Alexandre Santos (2020)
At Instituto de telecomunicações of Universidade de Aveiro was implemented a testbed in the rooftop of building 1. This testbed, called AMazING (Advanced Mobile wireless Network playGround) is composed of 24 fixed nodes and 1 mobile node that moves in a robot in a rail. This testbed apart from more traditional tests allows to testing mobility scenarios. This master thesis focus on the development of a platform that allows the creation of experiments related to the robot, allowing its control and subsequent data collecting and processing. The implementation includes tools such as web frameworks, like Django and Flask, REST, 3D modeling and embedded systems.